The antioxidant barrier, oxidative/nitrosative stress, and protein glycation in allergy: from basic research to clinical practice - Biedrzycki, Grzegorz; Wolszczak-Biedrzycka, Blanka; Dorf, Justyna; Maciejczyk, Mateusz (Frontiers in Immunology, 2024)
Recent studies indicate that oxidative/nitrosative stress is involved in the pathogenesis of asthma, allergic rhinitis, atopic dermatitis, and urticaria. The article aimed to review the latest literature on disruptions in redox homeostasis and protein glycation in allergy patients. It has been shown that enzymatic and non-enzymatic antioxidant systems are impaired in allergic conditions, which increases cell susceptibility to oxidative damage. Reactive oxygen/nitrogen species exacerbate the severity of asthma symptoms by activating inflammatory mediators that cause airway smooth muscle contraction, promote mucus hypersecretion, increase the permeability of lung capillaries, and damage cell membranes. Redox biomarkers could have considerable diagnostic potential in allergy patients. There is no compelling evidence to indicate that antioxidants reduce allergy symptoms’ severity or slow disease progression.